The results of glaucoma drainage tube surgery in patients with diabetes - Mukharram M. Bikbov; Ilnur I. Khusnitdinov (Сахарный диабет)
Aim. To compare the effectiveness of "Glautex" drainage and the Ahmed valve for the treatment of secondary neovascular glaucoma in patients with diabetes.Material and methods. We observed 28 eyes with neovascular glaucoma in 28 patients with proliferative diabetic retinopathy. The mean age of patients was 56.61 ± 1.43 years (range: 40–65). There were 11 males and 17 females. Patients were divided into two groups based on the drainage device used. The first group included 13 patients (13 eyes) for whom "Glautex" drainage was used, while the second group included 15 patients for whom the Ahmed valve model FP7 (New World Medical Inc., USA) was used.Results. The absolute hypotensive effect [normalization of intraocular pressure (IOP) without the use of drugs] 1 year after surgery was 46.1% (6/13) in group I and 60% (9/15) in group II. The relative hypotensive effect (normalization of IOP during treatment with glaucoma drugs) 1 year after surgery was 53.8% (7/13) in group I and 80% (12/15) in group II. Hyphema in the early postoperative period was observed in 30.7% (4/13) and 26.6% (4/15) of patients in groups I and II, respectively. Hypotension with choroid detachment was observed in 23.1% (3/13) of group I patients and 13.3% (2/15) of group II patients. Migration of the tube to the scleral layers occurred after implantation of the Ahmed valve in 6.6% (1/15) of patients.Conclusion. Comparative analysis of the outcomes of surgical treatment of secondary neovascular glaucoma in patients with diabetes showed that the most effective method to lower IOP was implantation of an Ahmed valve. The valve preserved visual function during the 1-year follow-up period and resulted in failed outcomes in only 20% of patients. The hypotensive effect of sinus trabeculectomy was observed in 53.8% of patients with "Glautex" drainage. There was a progressive decrease in visual function and the need for reintervention in 46.1% of group 1 patients.